Produk Agroindustri Olahan yang Berdaya Saing Ekspor dan Dampaknya terhadap PDRB Provinsi Jambi - Faradilla Herlin; M Rachmad R; Muhammad Safri (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2014)
The Objective of this research is two. firstly is to identify agro industry commodity oriented to export thah have excellent. secondly is to identify effect of industry development in terms of agro industry trough PDRB. As for this study is performed in Jambi Province. The methods used are descriptive quantitative. This analisis invelves two models. The first analysis use multile regression and the second analysis uses simple regression model. this analysis included, export price, competitor export price, exchange rates, national income and investment have influence to industry development as excellent agroindustry oriented to demand. The second, industry development as excellent agroindustry commodity has positive effect and real through inprovement of PDRB. Keywords: Agroindustry Product, Export Oriented